Model for Evaluating the Effectiveness of Cargo Operation Strategy in an Inland Container Terminal - Mateusz Zając; Tomislav Rozic; Ivona Bajor (Applied Sciences, 2023)
The paper discusses the issue of unproductivity during the implementation of operations in inland container terminals. The authors hypothesize that the two main factors influencing the number of unproductive manipulations are the adopted operating strategy and the occupancy level of the storage yard. The presented model classifies the operation time and the waiting time for container handling separately, and also compares the impact of the terminal storage occupancy and selected strategies on the handling time. Based on the collected data, the impact of the number of occupied storage places and the frequency of repetition of operations on the average time of handling a freight unit are simulated. It is noticed that increasing the occupancy of the terminal area above 35% results in a significant increase in the frequency of repetition of operations. In the case of terminal area occupancy of about 50%, the average waiting time for service and the service of a freight unit itself may vary significantly, depending on the adopted strategies for the implementation of operations.